2010
DOI: 10.1098/rsbl.2010.0384
|View full text |Cite
|
Sign up to set email alerts
|

Eavesdropping in crabs: an agency for lady detection

Abstract: Although conspicuous courtship displays are an effective way of attracting the attention of receptive females, they could provide valuable information to rival males on the location of these females. In fiddler crabs, males that see a receptive female wave their single, greatly enlarged claw in a highly conspicuous courtship display. We test whether other males use this courtship display to alert them to the presence of receptive females that they cannot directly see. We show that male fiddler crabs (Uca mjoeb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 15 publications
2
22
0
Order By: Relevance
“…respond to male courtship displays by initiating courtship (presumably exploiting signals to intercept a female), which is consistent with common definitions of eavesdropping behaviour (McGregor, 2005). While most examples of eavesdropping have come from vertebrate animals (see McGregor, 2005), it appears that some invertebrates also show this ability (Aquiloni, Bu ri c, & Gherardi, 2008;Aquiloni & Gherardi, 2010;Bailey & Field, 2000;Fitzsimmons & Bertram, 2013;Milner, Jennions, & Backwell, 2010Pope, 2005). A number of previous studies have demonstrated that eavesdropping has fitness benefits, particularly when mate location and/or assessment costs limit reproductive success.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…respond to male courtship displays by initiating courtship (presumably exploiting signals to intercept a female), which is consistent with common definitions of eavesdropping behaviour (McGregor, 2005). While most examples of eavesdropping have come from vertebrate animals (see McGregor, 2005), it appears that some invertebrates also show this ability (Aquiloni, Bu ri c, & Gherardi, 2008;Aquiloni & Gherardi, 2010;Bailey & Field, 2000;Fitzsimmons & Bertram, 2013;Milner, Jennions, & Backwell, 2010Pope, 2005). A number of previous studies have demonstrated that eavesdropping has fitness benefits, particularly when mate location and/or assessment costs limit reproductive success.…”
Section: Discussionmentioning
confidence: 99%
“…For example, females may reduce time invested in mate assessment by eavesdropping on male contests and/or copying mate choices of others (Aquiloni & Gherardi, 2010;Dugatkin, 1992;Dugatkin & Godin, 1993;Earley & Dugatkin, 2005;Peake et al, 2001). Males, on the other hand, might reduce costs of mate searching and compete more effectively by eavesdropping and initiating displays whenever courtship is detected, although there is less empirical support (Doutrelant & McGregor, 2000;Farr, 1976;Galef, 1988;Milner et al, 2010;Waas, 1988;Zajonc, 1965). Results of our studies suggest eavesdropping may be a form of competitive interference (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, coupling ( D ) is another factor that showed unexpected patterns where its increase does not always result in higher synchrony ( r ). In fact, the influence of other waving crabs in field might be a highly complex and variable aspect [67], [68].…”
Section: Discussionmentioning
confidence: 99%
“…8; see results). Fiddler crabs have an interesting framework where females likely chose males that wave first in a synchronic group as an indicator of male quality [24], [25], [30], [32], [33], [67]. Considering that this very unlikely visually limited situation is set, maybe due to physical visual barriers, where one male waves alone without seeing the others that follow him, a passing female which could assess all crabs in this group would chose the leader, even if all males in the synchronic group have same physical strength and stamina.…”
Section: Discussionmentioning
confidence: 99%
“…Earley and Dugatkin 2002), birds (Mennill et al 2002), dolphins (Götz et al 2006) and primates (Crockford et al 2007). Only recently was social eavesdropping described in two invertebrate species: the crayfish Procambarus clarkii Aquiloni and Gherardi 2010) and the fiddler crab Uca mjoebergi (Milner et al 2010). Females of P. clarkii learn who the winner is at the individual level by watching a pair of size-matched males fighting and then use this information to choose the dominant as a mate.…”
Section: Introductionmentioning
confidence: 99%